Analisis Kesalahan Siswa Madrasah Aliyah dalam Menyelesaikan Soal Materi Eksponen Berdasarkan Prosedur Kastolan - Susanti, Wiwit; Kartini, Kartini (MAN Insan Cendekia Siak, 2025)
Mathematics is an essential subject for students because it develops logical and analytical thinking skills, which form the foundation for understanding other concepts in mathematics as well as other scientific disciplines. One of the important topics in mathematics is exponents, which serve as a prerequisite for understanding other advanced topics. As prerequisite material, students are still frequently found to make errors in solving exponent problems. Therefore, this study aims to analyze students' errors in solving a number of exponent problems using the Kastolan procedure. This study uses a qualitative descriptive method with the research subjects consisting of 10 tenth-grade students from a Madrasah Aliyah (MA) in Siak Regency. The research instrument consists of 5 descriptive questions on exponent material. The data analysis techniques applied include data reduction, data presentation, and drawing conclusions. Based on the research findings, it is concluded that students made the following errors: conceptual errors, which involve students' inability to apply the correct properties of exponents; procedural errors, where students are unable to complete the steps needed to arrive at a final solution; and technical errors, which occur due to miscalculations that result in incorrect answers